Ignoring learners : an exploration of coping strategies among stressed teachers in rural secondary schools in the Vhembe district - Mulaudzi, Israel C.; Kutame, Azwidohwi P.; Hlongwane, Mandla M; Lawrence, Kehinde Clement (Penerbit Universiti Kebangsaan Malaysia, 2021)
The main aim of this study was to examine the coping strategies used by stressed teachers in the rural secondary schools in the Vhembe district, Limpopo province, South Africa. Being a qualitative design, eight rural secondary school teachers were purposively selected from three randomly selected schools. The individual interview technique was used to collect data from the participants. The findings revealed that the teachers in the rural secondary schools commonly used avoidance, personal resilience and problem-focused stress coping strategies to deal with stress; furthermore, effective teacher stress management strategies do not necessarily improve teaching performance, as factors such as a lack of teaching facilities, poor teacher remuneration, learner absenteeism, poor infrastructure and poverty, among other factors that are not addressed. The study concludes that the stressful nature of the teaching profession should be communicated earlier to prospective in-service teachers prior to graduation or the commencement of one’s teaching career. In addition, rural teachers should be trained on how to transform stressful experiences into opportunities through the application of the identified stress coping strategies, thus promoting the development of robust personal resources for teaching effectiveness and the realisation of education objectives.